The Union Club. - (:unkn) unknown (Fores, S. W., 1801)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Great Britain -- Politics and government -- 1800-1837; Ireland -- History -- Union, 1801